Primary abdominal pregnancy following intra-uterine insemination - Sujata Kar (Wolters Kluwer Medknow Publications, 2011)
Primary abdominal pregnancy is an extremely rare type of extrauterine pregnancy. It has been reported from many unusual intra-abdominal sites. We report a case of primary abdominal pregnancy following intra-uterine insemination (not reported earlier to our knowledge). Implanted on the anterior surface of the uterus possibly related to an endometriotic foci. Early diagnosis enabled laparoscopic management of this case.